HAJI MABRUR DALAM PARADIGMA FIKIH SOSIAL SUFISTIK - Athoillah Islamy (Balai Penelitian dan Pengembangan Agama Makassar, 2020)
AbstractThe biggest spiritual orientation for every Muslim in performing Hajj is getting predicate Hajj Mabrur. So whether the predicate is just a spiritual title? This research will describe Nurcholish Madjid's Sufistic social fiqh thoughts about the meaning of the predicate hajj Mabrur. This type of research is a qualitative research in the form of library research. The main data source used was a book by Nurcholish Madjid entitled Hajj and Umrah. Meanwhile, secondary sources are used, namely various studies that are relevant to the focus of this research study. The method used in this study is the method of interpreting the thought of figures. There are two big conclusions of this research. First, the integrative paradigm of nurcholish Madjid, namely the paradigm of integration between fiqh, social and Sufism. This integrative paradigm according to Nurcholish Madjid can make fiqh as a medium for the social reform movement. Second, the predicate Hajj Mabrur in the perspective of Nurcholish Madjid is not a predicate based on success in fulfilling the formal legal of the Hajj fiqh, but rather a predicate that has spiritual and social implications in social life.Keywords: Hajj mabrur, fiqh, social, sufismAbstrakOrientasi spritual terbesar bagi setiap muslim dalam menunaikan ibadah haji yakni mendapatkan predikat haji mabrur. Lantas apakah predikat tersebut hanya sekedar predikat spritual? Penelitian ini akan mendiskripsikan pemikiran fikih sosial sufistik Nurcholish Madjid tentang makna predikat haji mabrur. Jenis penelitian ini merupakan penelitian kualitatif yang berupa kajian pustaka (library research). Sumber data utama yang digunakan, yakni buku karya Nurcholish Madjid yang berjudul Haji dan Umrah. Sementara itu, sumber sekunder yang digunakan, yakni berbagai penelitian yang relevan dengan fokus kajian penelitian ini. Metode yang digunakan dalam penelitian ini, yakni metode interpretasi pemikiran tokoh. Terdapat dua kesimpulan besar penelitian ini. Pertama, paradigma fikih integratif nurcholish Madjid, yakni paradigma integrasi antara fikih, sosial dan tasawuf. Paradigma integratif ini lah yang menurut Nurcholish Madjid dapat menjadikan fikih sebagai medium gerakan reformasi sosial. Kedua, predikat haji mabrur dalam perspektif Nurcholish Madjid bukanlah sebuah predikat yang berdasarkan pada keberhasilan dalam memenuhi legal formal fikih ibadah haji, melainkan sebuah predikat yang memiliki implikasi spritual (tasawuf) dan sosial dalam kehidupan bermasyarakat. Kata Kunci : Haji mabrur, fikih, sosial, tasawuf